Euro Visions : Cyprus / Estonia / Hungary / Latvia / Lithuania / Malta / Poland / Czech Republic / Slovakia / Slovenia by ten Magnum Photographers - Dufour, Diane; Bajac, Quentin (Paris : Magnum/Steidl, 2005)
De Keyzer, Carl ; Franck, Martine ; Majoli, Alex ; Marlow, Peter ; Parr, Martin ; Power, Mark ; Sarfati, Lise ; Steele-Perkins, Chris ; Wylie, Donovan ; Zachmann, Patrick
Euro Visions exhibition, Centre Pompidou, Paris, september 15 - october 17 2005
boek